Feasibility of biodiesel as microturbine alternative fuel through atomization characteristics study - Tan E.S.; Zulhairi M.A. (2023)
The world is facing critical energy concern, in view of depleting fossil fuel reserves and increasing environment pollution. Biodiesel is a promising substitute that can reduce our dependence on fossil fuel. The application of biodiesel in microturbines is a new approach in the power generation industry. There are limited data at present on the potential of biodiesel in non-transportation sectors, where substantial energy and environment benefits exist. The objective of this paper is to study the feasibility of biodiesel to substitute conventional microtubine fuel through an atomization characteristics study in a fuel spray atomizer. Various blends of biodiesel derived from waste vegetable oil were tested experimentally in a fuel spray atomizer, to obtain main atomization characteristics such as Sauter Mean Diameter, spray angle and spray tip penetration. From the fuel properties analysis, it was found that the higher content of biodiesel gives higher viscosity, density and surface tension of the fuel. This will result in larger droplet size and longer spray length but smaller spray angle and spray width with clearer vortex shape of spray pattern in the atomization test experiment. Meanwhile, higher injection pressure during atomization testing process tend to break up fuel particles into smaller partition, which will subsequently produce larger spray angle and spray width but shorter spray length with denser spray pattern. The results of the experiment proved that biodiesel is a viable alternative fuel to gas turbine applications. Copyright 2012 by ASME.